(untitled) (Annals of Medical Research, 2021)
Aim: Acute upper gastrointestinal system hemorrhage is a common and life-threatening condition, and its mortality may reach 10% despite developing medical facilities. In this study, we aimed to compare the efficacy of the AIMS65 risk scoring and Rockall scoring in the non-variceal upper gastrointestinal hemorrhage patients and investigate the relationship between C-reactive protein/albumin ratio and these scoring systems.Materials and Methods: Forty-two inpatients diagnosed with upper gastrointestinal system hemorrhage in our hospital’s Internal Medicine Department between January 2018 and July 2018 included to study. For each patient, AIMS65 scoring according to the first evaluation results in the emergency department and Rockall scoring after the endoscopy were performed.Results: Mortality was observed in 2 (4.8%) patients. Both scoring systems were not statistically significant in determining the need for transfusion and predicting the hospitalization duration. The mean C-reactive protein/albumin ratio of the patients was found to be 0.94 (0.48-77.83), and C-reactive protein/albumin levels were higher in patients with high AIMS65 score (p=0.005).Conclusion: Upper gastrointestinal hemorrhage is a common emergency problem, and it constitutes 80% of all gastrointestinal system hemorrhages. In our study, the C-reactive protein/albumin ratio was consistent with the AIMS65 score and suggested that it could be a parameter that could be used in patients with upper gastrointestinal system hemorrhage, but more extensive studies are needed on this subject.Keywords: AIMS65; hemorrhage; rockall; scoring system.